ACOUSTIC EMISSIONS AT THE INSTANT DESTRUCTION OF THE CUTTING TOOL - Філоненко, С.; Косицка, Т.; Німченко, Т. (Science-based technologies, 2012)
The outcomes of simulation of acoustic emission resulting signal are reviewed, which one is reshaped at machine work of cutting material, with allowance of instantaneous composite material destruction. Is shown, that at instantaneous destruction of composite material on an acoustic emission resulting signal there is appearance of let of amplitude. Influencing the area of instantaneous destruction of composite material on value of acoustic emission resulting signal of let of amplitude is determined. The estimations ratio of signals parameters are conducted and is rotined, that at the small areas of composite material destruction there is no contribution of a reshaped pulse of acoustic emission signal to a resulting signal.